2021
DOI: 10.1093/emph/eoaa049
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum depression and mother–offspring conflict over maternal investment

Abstract: Structured Abstract Background and objectives As the mother-offspring relationship is central to human reproduction, postpartum depression symptoms are difficult to explain in evolutionary terms. We proposed that postpartum depression might arise as a result of evolutionary mother-offspring conflict over maternal investment, and investigated the association between postpartum depression symptoms, infant night waking, maternal sleep disturbance and breastfeedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 68 publications
0
5
0
1
Order By: Relevance
“…Pszichés gátak: A szoptatás erősíti az anya és az újszülött kötődését, támogatja az anyai kompetenciaérzést, csökkenti a szülés utáni depresszió előfordulását [44], enyhítheti a szorongásos tüneteket -bár az ok-okozati összefüggések feltárása még várat magára [45,46]. Amennyiben az anyacsecsemő diád egymásra hangolódása pszichés problémák következtében sikertelen, funkcionális problémák, táplálási, emésztési, alvási gondok léphetnek fel a csecsemőnél, mely esetekben első lépésként védőnő, laktációs szaktanácsadó és integrált szülő-csecsemő konzulens bevonása és együtt-működése segíthet.…”
Section: Példák Az Interdiszciplinaritás Szükségességére a Szoptatástámogatásbanunclassified
“…Pszichés gátak: A szoptatás erősíti az anya és az újszülött kötődését, támogatja az anyai kompetenciaérzést, csökkenti a szülés utáni depresszió előfordulását [44], enyhítheti a szorongásos tüneteket -bár az ok-okozati összefüggések feltárása még várat magára [45,46]. Amennyiben az anyacsecsemő diád egymásra hangolódása pszichés problémák következtében sikertelen, funkcionális problémák, táplálási, emésztési, alvási gondok léphetnek fel a csecsemőnél, mely esetekben első lépésként védőnő, laktációs szaktanácsadó és integrált szülő-csecsemő konzulens bevonása és együtt-működése segíthet.…”
Section: Példák Az Interdiszciplinaritás Szükségességére a Szoptatástámogatásbanunclassified
“…One of the studies was conducted in Pekanbaru City, Riau Province showing that 16.7% of postpartum mothers had PPD (Misrawati et al, 2014). Another study by Desfanita et al, 2015 showed that most mothers experienced PPD with a total of 40 respondents (53.3%) (Gunst et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that infant night waking to breastfeed could be an adaptive strategy by the offspring to lengthen the IBI by suppressing the mother’s fertility ( Haig, 2014 ; Jones et al, 1987 ). A recent study by Gunst et al (2021) suggested that infant night waking could be an adaptation to lengthen the IBI by exhausting the mother through disturbed sleep. The authors hypothesized that mothers exhausted by their offspring would be less likely to conceive and gestate additional offspring (e.g., by decreasing the mother’s sex drive, De Judicibus & McCabe [2002 ]; or by decreasing her fertility by hypothalamic-pituitary-adrenal activation, White [2016 ]), consequently extending the IBI.…”
Section: Introductionmentioning
confidence: 99%
“…The authors hypothesized that mothers exhausted by their offspring would be less likely to conceive and gestate additional offspring (e.g., by decreasing the mother’s sex drive, De Judicibus & McCabe [2002 ]; or by decreasing her fertility by hypothalamic-pituitary-adrenal activation, White [2016 ]), consequently extending the IBI. Moreover, according to Gunst et al (2021) , postpartum depression symptoms could in this case be a result of mother-offspring conflict. Bearing in mind the negative impact that postpartum depression has for both the mother’s and the infant’s fitness ( Slomian et al, 2019 ), it is from an evolutionary perspective hard to grasp why it is so prevalent, affecting up to 15% of mothers ( Gavin et al, 2005 ; Shorey et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation